Effects of Posture Change on the Geometry and Hemodynamics of the Human Carotid Bifurcation - Αριστοκλέους, Νικόλας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
Cardiovascular diseases (CVD), especially atherosclerosis, continue to be the leading cause of morbidity and mortality and the principal cause of death in the United States, Europe and most of Asia. Scientific research in this field over the last few decades shows that vessel geometry and hemodynamic forces influence vascular pathology. As it is well known, regions of disturbed and oscillatory flow in the circulatory system, like bifurcations and arches, are characterized by low shear stresses, which allow the atherogenesis and the development of atherosclerotic lesions. In general, the nature of the blood flow plays an essential role in determining whether atherosclerotic lesions occur at various vascular sites. This study focuses on the morphological changes of human carotid bifurcation (CB) that may occur as the head is rotated in different postures. These morphological changes of the bifurcation geometry may cause alterations in the blood flow field within the CB and consequently lead to the initiation and/or to the further development of the disease. The first part of the thesis focuses on the literature review and the theoretical study of the physiology of human carotid bifurcation and the diseases developed in this area, specifically atherosclerosis, and their relation to hemodynamic parameters. It also provides an overview of the basic theory of biofluid dynamics and Magnetic Resonance Imaging (MRI). The second part presents the work done using medical image acquisition and processing for the construction of three dimensional (3D) surface models. More specifically, by using MR images of human individuals and employing segmentation techniques, the construction of realistic 3D surface models was feasible. This was done to investigate the bifurcation region, and in more detail to assess the geometric changes of normal human carotid bifurcations. Initially, the geometric alterations were estimated for the right and left carotid artery bifurcation (RCA and LCA respectively) in the case of ten volunteers, in two head positions, the neutral supine (SP) and the prone position with rightwards head rotation up to 80 degrees (PPRR). In addition, a third head position was vii investigated in the case of two out of the ten volunteers, the prone position with leftwards head rotation up to 80 degrees (PPLR). The first step was to construct accurate CB models using MR images and to quantify the important geometric features of each model in order to investigate the differences between the supine position and the prone with head rotation. The next step was to use the extracted information from the medical images. This information is in the form of spatial pixel coordinates and intensities that determine the boundaries of the wall and lumen of the carotid arteries. Using this information and by employing specialized segmentation software, the 3D carotid models were constructed consisting of the common carotid artery (CCA), the internal carotid artery (ICA) and the external carotid artery (ECA). Next, using vascular model toolkit (VMTK) software I was able to calculate the following geometric features of each model: a) the bifurcation angle; b) the ICA angle; c) the planarity angle; d) the asymmetry angle; e) the tortuosity; e) the curvature; f) the bifurcation area ratio; h) the ICA/CCA diameter ratio; i) the ECA/CCA diameter ratio; and j) the ECA/ICA diameter ratio. The results obtained have demonstrated that head rotation positions lead to random and frequent significant changes in geometric parameters. The changes observed may also cause significant changes in the bifurcation hemodynamics environment which is related to the initiation and the development of atherosclerotic disease. In the third part of the thesis, the evaluation of the influence of head rotation on the flow characteristics took place, with the use of computational fluid dynamics (CFD). More specifically, with a specialized meshing software (ICEM-CFD), using the carotid surface models I proceeded to the construction of the corresponding CB meshes. These were necessary to solve the equations governing the blood flow, which was achieved using the finite volume method. The numerical calculation of the important hemodynamic parameters related with atherosclerosis was carried out on a subject-specific basis in two extensive studies. First, I performed CFD simulations on two volunteers using the same inlet velocity waveform as boundary condition. What I investigated were the changes on RCA and LCA in the three head positions (SP, PPLR and viii PPRR). In the second study and on the same volunteers, I performed CFD simulations using the realistic inlet velocity waveform. The results indicated that torsion of the head causes notable changes in spatial distribution of wall regions exposed to unfavorable hemodynamics. Another conclusion was that the effect of geometry on the hemodynamic features was more significant than that of the inlet waveform. The main conclusion of the thesis is that the head and neck postures may cause significant morphological changes on human CB. These geometric alterations lead to blood flow field alterations, which may be associated with the initiation and development of atherosclerotic disease.
Keywords: Cardiovascular Diseases; Carotid Bifurcation